Real-time motion control of robotic manipulators for safe human–robot coexistence. (February 2022) - Merckaert, Kelly; Convens, Bryan; Wu, Chi-ju; Roncone, Alessandro; Nicotra, Marco M.; Vanderborght, Bram
Abstract: This paper introduces a computationally efficient control scheme for safe human–robot interaction. The method relies on the Explicit Reference Governor (ERG) formalism to enforce input and state constraints in real-time, thus ensuring that the robot can safely operate in close proximity to humans. The resulting constrained control method can steer the robot arm to the desired end-effector pose (or a steady-state admissible approximation thereof) in the presence of actuator saturation, limited joint ranges, speed limits, static obstacles, and humans. The effectiveness of the proposed solution is supported by theoretical results and numerous experimental validations on the Franka Emika Panda robotic manipulator, a commercially available collaborative 7-DOF robot arm. Highlights: Real-time predictive constrained control with Explicit Reference Governor. Robotic arm avoids actuator saturations, limited joint and velocity constraints. Guaranteed robot collision avoidance in static obstacle environments. Empirical robot collision avoidance in highly dynamic environments. Safe and performant human–robot coexistence with Franka Emika Panda.